Metagenomic sequencing of post-mortem tissue samples for the identification of pathogens associated with neonatal deaths - Baillie, Vicky L.; Madhi, Shabir A.; Ahyong, Vida; Olwagen, Courtney P. (Nature communications, 2023)
Postmortem minimally invasive tissue sampling together with the detailed review of clinical records has been shown to be highly successful in determining the cause of neonatal deaths. However, conventional tests including traditional culture methods and nucleic acid amplification tests have periodically proven to be insufficient to detect the causative agent in the infectious deaths. In this study, metagenomic next generation sequencing was used to explore for putative pathogens associated with neonatal deaths in post-mortem blood and lung tissue samples, in Soweto, South Africa. Here we show that the metagenomic sequencing results corroborate the findings using conventional methods of culture and nucleic acid amplifications tests on post-mortem samples in detecting the pathogens attributed in the causal pathway of death in 90% (18/20) of the decedents. Furthermore, metagenomic sequencing detected a putative pathogen, including Acinetobacter baumannii, Klebsiella pneumoniae, Escherichia coli , and Serratia marcescens , in a further nine of 11 (81%) cases where no causative pathogen was identified. The antimicrobial susceptibility profile was also determined by the metagenomic sequencing for all pathogens with numerous multi drug resistant organism identified. In conclusion, metagenomic sequencing is able to successfully identify pathogens contributing to infection associated deaths on postmortem blood and tissue samples. Rapid identification of pathogens in neonatal infection, and corresponding antimicrobial susceptibility profiles, would improve patient outcomes and assist in antibiotic stewardship. In this work, the authors utilize metagenomic next-generation sequencing of post-mortem tissue samples to identify pathogens associated with neonatal deaths.